Micro and Nanotechnologies for Biotechnology - Stanciu, Stefan G. (IntechOpen, 2016)
Countless healthcare and biomedical solutions with high impact in terms of timely diagnostics, therapeutic success, patient comfort or financial sustainability of healthcare systems rely on micro- and nanotechnologies. Thus, it is not at all exaggerate to claim that such technologies play in current days a tremendous role with respect to improving the quality of our life, health and well-being, which are the main priorities of modern science. This volume illustrates these statements, addressing highly significant scientific subjects from diverse areas of micro- and nanotechnologies for biotechnology. Authoritative voices in their fields present in this volume their work, or review recent trends, concepts and applications, in a manner that is accessible to a broad readership audience from both within and outside their specialist area.